2005
DOI: 10.1080/13548500512331315334
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of control over heart disease in people with an inherited predisposition to raised cholesterol

Abstract: This cross-sectional study aimed to describe the perception of control over heart disease, and the likely antecedents of this perception, in 340 people with an inherited predisposition to premature coronary heart disease. Dependent variables were self-efficacy and response efficacy. Independent variables were history of heart disease and current symptoms, current cholesterol level, emotional state, and causal attributions. Overall, levels of perceived personal control (self-efficacy) were moderately high and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 30 publications
3
12
1
Order By: Relevance
“…This is perhaps not surprising given that their personal experience may lead them to be more likely to state that the disease runs in families or to state that the disease is inherited to some extent. Our findings are consistent with clinical studies which have shown that individuals at increased personal or family history-based risk of heart disease have tended to hold stronger genetic causal beliefs about the disease [25,26,27]. A family history is strongly associated with individual risk and, therefore, people are correct to infer that genes contribute to their heart disease risk.…”
Section: Discussionsupporting
confidence: 80%
“…This is perhaps not surprising given that their personal experience may lead them to be more likely to state that the disease runs in families or to state that the disease is inherited to some extent. Our findings are consistent with clinical studies which have shown that individuals at increased personal or family history-based risk of heart disease have tended to hold stronger genetic causal beliefs about the disease [25,26,27]. A family history is strongly associated with individual risk and, therefore, people are correct to infer that genes contribute to their heart disease risk.…”
Section: Discussionsupporting
confidence: 80%
“…First, awareness of the role of lifestyle in causing heart disease is low even in these high risk populations [17,18,37,38]. Second, these populations have tended to have stronger beliefs that hereditary, genetic or biological factors cause heart disease than lifestyles [15,38,37].…”
Section: Discussionmentioning
confidence: 95%
“…First, awareness of the role of lifestyle in causing heart disease is low even in these high risk populations [17,18,37,38]. Second, these populations have tended to have stronger beliefs that hereditary, genetic or biological factors cause heart disease than lifestyles [15,38,37]. Although the views of the general public may differ substantially from the views of people already with or at high risk of heart disease, we found little evidence in the present study to suggest that people with a familial risk of heart disease held significantly different beliefs about the roles of lifestyle from people at average risk.…”
Section: Discussionmentioning
confidence: 99%
“…There is also some support that identifying a genetic predisposition to CVD strengthens genetic attributions of CVD while weakening attributions to behavioral causes (Marteau et al, 2004;Senior, Weinman, & Marteau, 2000). There is some evidence that the provision of genetic risk information increases perceived efficacy of medication (Marteau et al, 2004;Phelan, Yang, & Cruz-Rojas, 2006;Senior & Marteau, 2007;Senior, Marteau, & Weinman, 2005;Wright, Weinman, & Marteau, 2003) and decreases the perceived efficacy of a healthy lifestyle (Marteau et al, 2004;Senior & Marteau, 2007). Only a few studies have examined the role of having a family history of CVD and/or an identified genetic predisposition to CVD in relation to preventive behavior.…”
Section: Introductionmentioning
confidence: 92%